Acceptance Analysis and Application Success Bicarakan.id using Utaut and DeLone & McLean - Tegar Adi Wicaksono; Anita Wulansari; Rafika Rahmawati (Universitas Islam Kuantan Singingi, 2025)
The development of digital-based mental wellbeing administrations gives viable and adaptable arrangements for the community, particularly the millennial era, in getting to mental administrations. One of the stages that give online counseling administrations in Indonesia is the application Bicarakan.id, which demonstrates a decently tall selection rate. Be that as it may, based on perceptions, it was found that different complaints from clients on a number of stages, such as less than ideal application execution and moderate reaction from benefit suppliers, hence preventing get to to the specified administrations. This consider points to analyze the components that influence the acknowledgment and effective utilize of the application Bicarakan.id by combining two approaches,namely the Unified Theory of Acceptance and Use of Technology (UTAUT) and DeLone & McLean model. The examination prepare was conducted utilizing Partial Least Square Structural Equation Model (PLS-SEM) through SmartPLS 4 computer program and included 403 respondents. The comes about appeared that the factors Information Quality, Service Quality, and Effort expectation desire have a positive and critical impact on User Satisfaction, which in turn too have a positive and critical impact on Continuance Intention. In the mean time, factors System Quality and Performance Expectancy desire don't have a critical impact on User Satisfaction, as prove by testing Path Coefficient based on the centrality criteria set.